2019
DOI: 10.35329/agrovital.v3i2.203
|View full text |Cite
|
Sign up to set email alerts
|

Evaluasi Penentuan Waktu Tanam Padi (Oriza Sativa L.) Berdasarkan Analisa Curah Hujan Dan Ketersediaan Air Pada Wilayah Bedungan Sekka-Sekka Kabupaten Polewali Mandar

Abstract: Tanaman  padi merupakan tanaman penting dan strategis di Indonesia. Kebutuhan pangan khususnya beras mengalami peningkatan setiap tahunnya. Salah satu unsur iklim yang sangat mempengaruhi pertumbuhan dan produksi padi adalah curah hujan. Produktivitas rata-rata tanaman padi berkisar 5,14 t /ha.  Padahal, potensi produktivitas tanaman padi dapat mencapai 10-11 t/ha.  Salah satu penyebabkan rendahnya produktivitas tersebut adalah ketersediaan air khususnya pada musim kemarau. Upaya yang bisa diakukan untuk menga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…(Sahih Muslim 2363) One of the factors that influences rice growth and production is rainfall. Therefore, farmers need to evaluate the optimisation of planting times based on rainfall analysis and water availability (Karim, 2018). For this reason, the people of Kampung Naga determine the planting time to be in January and July.…”
Section: The Context Of Pamali Religiousity In the Kampung Naga Commu...mentioning
confidence: 99%
“…(Sahih Muslim 2363) One of the factors that influences rice growth and production is rainfall. Therefore, farmers need to evaluate the optimisation of planting times based on rainfall analysis and water availability (Karim, 2018). For this reason, the people of Kampung Naga determine the planting time to be in January and July.…”
Section: The Context Of Pamali Religiousity In the Kampung Naga Commu...mentioning
confidence: 99%
“…Using the Mamdani fuzzy method, the continuous defuzzification variable uses equation (1), while for discrete variables it uses equation (2). The centroid rule is a way of taking the center point of the set [6].…”
Section: Fuzzy Mamdanimentioning
confidence: 99%
“…Sources of income from agricultural products have an important role, including food crops such as rice, corn, peanuts, soybeans which are important for national-scale security [1]. The thing that causes crop failure will occur if it is not following the right planting time in farming [2]. Research conducted by Ahmad Ridha and Sulaiman was carried out to determine the difference between revenues and costs by using the jajar legowo planting system with the traditional planting system, from the study obtained difference that the jajar legowo rice planting system showed a more appropriate level of opinion than the jajar legowo rice planting system.…”
mentioning
confidence: 99%
“…Residues of fertilisers and pesticides can last a long time in the soil and cause compaction, soil acidity, and lack of nutrient availability [17]. In addition, farmers make maximum use of land to plant rice continuously regardless of climate type and cropping pattern [18].…”
Section: Introductionmentioning
confidence: 99%
“…Until now, the existing research has only focused on improving soil quality without considering the factors that affect the land [19]; [12]; [20]. Other research concentrates only on individual disciplines such as erosion, climate assessment, and cropping pattern determination [4]; [18]; [21]; [22].…”
Section: Introductionmentioning
confidence: 99%